2011
DOI: 10.1029/2010jc006700
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of the cross-shore flow structure in the surf and swash zones

Abstract: The flow structure of oscillatory broken waves within surf and swash zones was investigated using particle image velocimetry (PIV) in the laboratory. With the resolved spatial distribution of the velocity field, vorticity was computed directly. The results show that flow separation at the bed occurs during the interaction between the uprush bore front and the downwash flow. The separation point advances in the onshore direction with the bore front until the bore reaches the lowest point of the moving shoreline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…Moreover, the peak uprush and backwash s xz magnitudes result in 80.8 N m -2 and 12.7 N m -2 , which compare to 77.8 N m -2 and 16.9 N m -2 for the impermeable case. Sou and Yeh [2011] investigated the ensemble-averaged vorticity field under plunging breakers in the surf and swash zones using PIV measurements. Their study validated the vorticity as an effective property to evaluate mechanisms that result from the combined action of pressure gradients, body forces at the water surface, and drag forces at the water-bed interface.…”
Section: 1002/2015jc010806mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the peak uprush and backwash s xz magnitudes result in 80.8 N m -2 and 12.7 N m -2 , which compare to 77.8 N m -2 and 16.9 N m -2 for the impermeable case. Sou and Yeh [2011] investigated the ensemble-averaged vorticity field under plunging breakers in the surf and swash zones using PIV measurements. Their study validated the vorticity as an effective property to evaluate mechanisms that result from the combined action of pressure gradients, body forces at the water surface, and drag forces at the water-bed interface.…”
Section: 1002/2015jc010806mentioning
confidence: 99%
“…However, there are sub regions of alternating CCW and CW x near the surface indicating divergence/convergence patterns. Sou and Yeh [2011] also described advected CCW x at the surface inside the swash zone during the uprush phase which was related to wave-swash interactions in the inner surf zone. Here in the absence of wave-swash interactions, it is shown that local mechanisms are able to generate similar divergence/convergence patterns.…”
Section: Boundary Layer Growth Across the Swash Zonementioning
confidence: 99%
See 2 more Smart Citations
“…There have also been many experimental attempts to visualise coherent vorticity structures in boundary layers or in rotating flows, but only a few in the bulk of fairly homogeneous isotropic flows (Dernoncourt et al 1998). Sou and Yeh (2011) employed particle image velocimetry to investigate the fundamental characteristics of the flow structure in the vertical cross-shore plane as the wave evolves from the outer surf zone to the swash zone. They suggested that vorticity generated near the bed has a simple relation to the pressure gradient for boundary layer flows.…”
Section: R Mukaromentioning
confidence: 99%